A FUZZY-AHP AND GEOSPTIAL ANALYASIS MODEL FOR LAND SUITABILITY ASSESSMENT OF DATE PALM (Phoenix dactylifera) CULTIVATION IN NORTHREN BASARAH, IRAQ. - Al-Mayyahi , Mustafa Saleh Ali; Al-Attab, Salah Mahdi Sultan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was executed in the northern part of Basrah Governorate in southern Iraq to evaluate the suitability of lands for date palm cultivation by integrating fuzzy logic, remote sensing, and geographic information systems. Nine criteria were studied, including chemical properties (EC, pH, O.C, CaCO₃, and CEC) and physical properties encompassing soil particle size distribution, soil depth, and soil bulk density, in addition to the supervised classification map. The importance and influence of all criterion have been determined through a Multi-Criteria Decision-Making (MCDM) method. Fuzzy logic was then employed to develop a specific mathematical model for evaluating land suitability for date palm cultivation and to produce a land suitability map for study area. 73.96% of the studied lands are unsuitable (N1), while moderately suitable (S2) lands constituted 15.45%, and marginally suitable (S3) lands constituted 10.59%. Lands that classified as S1 were missed due to urban expansion, high soil salinity, high carbonate minerals, and unsuitable soil depth for date palm cultivation. moreover, the developed mathematical equation can be applied to assess land suitability for date palm cultivation in areas with similar conditions to the study area.